Guide system based users' intentions for a humanoid robot - CHAE, YU JUNG; Choi, JongSuk; ChangHwan, Kim; Yun, Sang-Seok (2016 13TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS AND AMBIENT INTELLIGENCE (URAI), 2016)
In the field of human-robot interaction, it is important to attract user's interests. In this regard, it is useful to use gaze and pointing gesture to read and lead to intentions. However, there are not sufficient to studies that generate behaviors according to recognized users' intentions. Furthermore, it is difficult to select suitable behavior considering changing user's state. In this paper, we propose a method that is to guide user's decision using robot's gaze and pointing gestures.